Branching ratio coherent control in ultrafast bond making - Amitay, Z.; Liat, L.; Reich, D. M.; Kosloff, R.; Koch, Christiane P. (Journal of Physics: Conference Series, 2020)
Coherent control of bond making (photoassociation) is crucial for the realization of a new photochem-istry, where a lasereld is actively photo-driving the irradiated system in a coherent way from the initial state of reactants to the final state of desired products. In a significant step forward, we experimentally demonstrate here coherent control over the photoassociation branching ratio to different target states of the generated molecule. The model process is strong-field multiphoton femtosecond photoassociation of thermally hot magnesium atoms into bound magnesium dimer molecules.
CRIS-Team Scopus Importer:2023-04-20